Reproductive biology and population structure of white warehou Seriolella caerulea and silver warehou Seriolella punctata in the austral zone off Chile - Liu Chong; Andrés Flores; Juan Carlos Quiroz; Francisco Contreras; Rodrigo Wiff (Journal of Fish Biology, 2019)
Using an extensive database compiled by scientific observers aboard commercial fishing operations between 1984 and 2014, we describe the maturity and size structures of white warehou Seriolella caerulea and silver warehou Seriolella punctata from by‐catch of the trawling industrial fisheries operating in the austral zone off Chile. Macroscopic maturity stages and gonadosomatic ( I GS ) index show mature females throughout the year and a pronounced spawning period in both austral autumn and winter seasons, with an I GS peak in July for S. punctata and August for S. caerulea . Reproductive patterns in both species show an extended spawning season (July to September) across the area between 43 and 47° S. Length–mass relationships showed significant differences between sexes in both species, where females reach a larger size. Fork length at 50% maturity was 43.5 cm for S. caerulea and 37.2 cm for S. punctata . Female catch composition is dominated by adult fish (96% for S. caerulea and 86% for S. punctata) . Currently, both species are exploited with no assessment and management‐decision framework. Therefore, information regarding reproductive biology and demographic traits becomes an important baseline to ensure adequate fisheries management for both species.